Mad River, Marjorie Rowland, and the quest for LGBTQ teachers' rights - Nash, Margaret A., 1959-; Graves, Karen, 1959- (New directions in the history of education., 2022)
"Mad River, Marjorie Rowland, and the Quest for LGBTQ Teachers' Rights addresses an important legal case that set the stage for today's LGBTQ civil rights-a case that almost no one has heard of. Marjorie Rowland v. Mad River School District involves an Ohio guidance counselor fired in 1974 for being bisexual. Rowland's case made it to the U.S. Supreme Court, but the justices declined to consider it. In a spectacular published dissent, Justice Brennan laid out arguments for why the First and Fourteenth Amendments apply to bisexuals, gays, and lesbians. That dissent has been the foundation for LGBTQ civil rights advances since. In the first in-depth treatment of this foundational legal case, authors Margaret A. Nash and Karen L. Graves tell the story of that case and of Marjorie Rowland, the pioneer who fought for employment rights for LGBTQ educators and who paid a heavy price for that fight. It brings the story of LGBTQ educators' rights to the present, including commentary on Bostock v Clayton County, the 2020 Supreme Court case that struck down employment discrimination against LGBT workers"--